THE INFLUENCE OF WORKLOAD AND JOB STRESS ON EMPLOYEE PERFORMANCE AT CONCORD INDUSTRIAL COMPANY - Miranda Desti Fadhila Putri; Sari Marliani; July Yuliawati (PT. Berkah Digital Teknologi, 2024)
Purpose: To analyze the influence of workload and work stress on employee performance at PT. Concord Industrial Karawang, a company located in Karawang, known as the